Social translucence as a theoretical framework for sustainable HCI - Barreto, Mary (2022)
Motivating sustainable behaviors is increasingly becoming an important topic in the HCI community. While a substantial body of work has focused on the role of peer-pressure through social networks, we argue that the community has largely overlooked the importance of strong social ties and specifically those of family members. We propose the theory of Social Translucence as a theoretical framework for understanding how eco-feedback interfaces can integrate with and support existing communication practices within families. We report on our ethnographic inquiry involving a day reconstruction study followed by in-depth interviewing with 12 families, which took place during a six-month deployment of an eco-feedback interface. Through our study we attempt to inquire into how eco-feedback interfaces: a) raise mutual awareness of family members’ consumption behaviors, and b) induce feelings of accountability on individuals regarding their consumption behaviors.